Development of the Portal of Cultural Heritage Objects the Kingdom of Poland - KOVALEV, Evgeny; KOVALEVA, Natalia; SALEH, Hadi (Journal of Education, Technology and Computer Science, 2015)
The article discusses the need to create of the portal of cultural heritage theKingdom of Poland. The authors well founded the need to develop, held informationmodeling of the portal. The article describes the functionality of the portaland used technologies.